2002
DOI: 10.1007/s00125-002-0781-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of autoimmunity in Type I diabetes and associated disorders

Abstract: Type I (insulin-dependent) diabetes mellitus is a heterogeneous disease with major subdivisions termed Type 1A (immune-mediated) and Type 1B. Immunemediated diabetes is also heterogeneous with ªmono-genicº, oligogenic, and polygenic forms present in humans and in animal models. Single-gene mutations of two transcription factors have been recently identified in rare syndromes of autoimmunity with type 1A diabetes: autoimmune polyendocrine syndrome type 1 (APS-1) and X-linked polyendocrinopathy, immune dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
15

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 119 publications
(137 reference statements)
5
91
1
15
Order By: Relevance
“…MHC accounts for approximately 50% of the familiar risk for T1D. 34 The identity of the b57 residue is important both for disease susceptibility and protection: Ala, Ser or Val at b57 defines predisposing alleles such as DQ2, DQ8, I-A g7 and DR8, whereas Asp is found in protective allele DQ6. The structural explanation for the importance of b57 was obtained from the crystal structure of I-A k and I-A d where it was shown that Asp at b57 forms a salt bridge with an Arg at position 76 of the a-chain (homologous to position 79 on the DQa chain).…”
Section: Hla-dr8-binding Motif L Muixí Et Almentioning
confidence: 99%
“…MHC accounts for approximately 50% of the familiar risk for T1D. 34 The identity of the b57 residue is important both for disease susceptibility and protection: Ala, Ser or Val at b57 defines predisposing alleles such as DQ2, DQ8, I-A g7 and DR8, whereas Asp is found in protective allele DQ6. The structural explanation for the importance of b57 was obtained from the crystal structure of I-A k and I-A d where it was shown that Asp at b57 forms a salt bridge with an Arg at position 76 of the a-chain (homologous to position 79 on the DQa chain).…”
Section: Hla-dr8-binding Motif L Muixí Et Almentioning
confidence: 99%
“…Susceptibility is linked to HLA DQA and DQB genes, influenced by the DR genes [47]. The observation that certain breeds of dog are predisposed to diabetes suggests that there is also a genetic component to canine diabetes.…”
Section: Insulin Deficiency Diabetesmentioning
confidence: 99%
“…Genetic factors, mainly HLA DR-DQ genotypes, are strong susceptibility factors [6]. However, among newly diagnosed type 1 diabetes patients only 10 to 15% have a first-degree relative with the disease [7] and the concordance rate between monozygotic twins is low [8,9], underlining the importance of environmental factors.…”
Section: Introductionmentioning
confidence: 99%